2015
DOI: 10.1371/journal.pone.0129311
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Cardiometabolic Risk Factors Is Not Associated with Microalbuminuria in 14-to-20-Years Old Slovak Adolescents: A Cross-Sectional, Population Study

Abstract: IntroductionIn adults, microalbuminuria indicates generalized endothelial dysfunction, and is an independent risk factor for cardiovascular and all cause mortality. Slovak adults present one of the highest cardiovascular mortality rates in Europe. Thus Slovak adolescents are on a high-risk to develop cardiovascular afflictions early, and screening for microalbuminuria might be useful in early assessment of their cardiovascular risk. We aimed to study the prevalence of microalbuminuria in Slovak adolescents, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…In addition, Invitti et al (2006) found that MA was associated with metabolic syndrome. However, one large study found no association between MA and any cardiovascular risk factor (Gurecka et al 2015). Cho and Kim (2017) studied the associations with similar study population to ours, and suggested that MA can be a helpful cardiovascular disease risk marker.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In addition, Invitti et al (2006) found that MA was associated with metabolic syndrome. However, one large study found no association between MA and any cardiovascular risk factor (Gurecka et al 2015). Cho and Kim (2017) studied the associations with similar study population to ours, and suggested that MA can be a helpful cardiovascular disease risk marker.…”
Section: Discussionsupporting
confidence: 66%
“…Some studies found that obese adolescents were more likely to develop MA as adults (Csernus et al 2005;Burgert et al 2006;Invitti et al 2006). On the other hand, recent large-scale studies came to the opposite conclusion (Nguyen et al 2008;Gurecka et al 2015). For example, in the National Health and Nutrition Examination Survey, the prevalence of MA was lower in obese than in normal-weight adolescents unlike adults (Nguyen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The cross-sectional BRespect for Health^study was carried out in students attending state-governed secondary schools in Bratislava Region, as described in detail previously [31]. It aimed to characterize cardiometabolic health status of adolescents, to implement an effective preventive program for early protective regimens.…”
Section: Methodsmentioning
confidence: 99%
“…Anthropometric and blood pressure (BP) measurements were performed at schools by trained medical personnel, as described previously [31]. Briefly, body weight and percentage of total body fat (TBF, bioimpedance method) were determined using digital scales (Omron BF510); height and waist circumference were measured.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation